Juridical Analysis of the Normative Gap in the Summoning of A Charge and A De Charge Witnesses in Indonesia - Manurung, Arthur Kusuma Atmaja; Prasetyawan, Tegar Eka; Setiawan, Frans; Rahman, Alip; Nurhaqi, Ari (Journal of Legal and Cultural Analytics, 2025)
The Public Prosecutor, as the representative of the State, holds dominant authority in regulating the course of criminal trials (dominus litis). The role of the Prosecutor inevitably places them in direct opposition to the interests of the Defendant. This clearly demonstrates a disparity in how the law treats the summoning of witnesses: while the Prosecutor’s witnesses are compelled by law, those of the Defendant are not equally supported or guaranteed by the legal framework. As a result, the Defendant’s right to present mitigating witnesses remains a theoretical entitlement (lex scripta) without enforceability. This research conducts a normative juridical analysis of relevant legal texts, scholarly literature, and journal sources. A significant imbalance is evident in the process of summoning witnesses those summoned by the Prosecutor aim to incriminate (a charge), while those proposed by the Defendant seek to mitigate or exculpate (a de charge). Incriminating witnesses are bound by legal obligations and face sanctions under Article 224 in conjunction with Article 552 of the Indonesian Penal Code if they fail to appear, and their testimony is considered valid evidence in court. The findings indicate that this legal imbalance significantly affects the objectivity of criminal proceedings, often leading to a tendency to disadvantage the defendant. In contrast, exculpatory witnesses are treated merely as a "right" of the Defendant, without any enforceable obligation to appear, as no legal consequences exist for their absence.